Saliva RNA Biomarkers of Gastrointestinal Dysfunction in Children With Autism and Neurodevelopmental Disorders: Potential Implications for Precision Medicine - Beversdorf, David Q.; Sohl, Kristin; Levitskiy, David; Tennant, Priscilla; Goin-Kochel, Robin P.; Shaffer, Rebecca C.; Confair, Alexandra; Middleton, Frank A.; Hicks, Steven D. (Frontiers in Psychiatry, 2022)
Gastrointestinal (GI) disorders are common in children with neurodevelopmental disorders such as autism spectrum disorder (ASD). A limited understanding of the biologic factors that predispose this population to GI disorders has prevented development of individualized therapies to address this important medical issue. The goal of the current study was to determine if elements of the salivary micro-transcriptome could provide insight into the biologic perturbations unique to children with ASD-related GI disturbance. This cohort study included 898 children (ages 18-73 months) with ASD, non-ASD developmental delay (DD), or typical development (TD). The saliva micro-transcriptome of each child was assessed with RNA-seq. Outputs were aligned to microbial and human databases. A Kruskal Wallis analysis of variance (ANOVA) was used to compare levels of 1821 micro-transcriptome features across neurodevelopmental status (ASD, DD, or TD) and GI presence or absence. An ANOVA was also used to compare micro-transcriptome levels among GI sub-groups (constipation, reflux, food intolerance, other GI condition, no GI condition), and to identify RNAs that differed among children taking three common GI medications (probiotics, reflux medication, or laxatives). Relationships between features identified in ANOVA testing were examined for associations with scores on the Autism Diagnostic Observation Schedule, 2nd Edition (ADOS-2) and the Vineland Adaptive Behavior Scales. GI disturbance rates were higher among children with ASD than peers with TD but were similar to those with DD. Five piwi-interacting RNAs and 3 microbial RNAs displayed an interaction between developmental status and GI disturbance. Fifty-seven salivary RNAs differed between GI sub-groups - with microRNA differences between food intolerance and reflux groups being most common. Twelve microRNAs displayed an effect of GI disturbance and showed association with GI medication uses and measures of behavior. These 12 microRNAs displayed enrichment for 13 physiologic pathways, including metabolism/digestion and neurobiology. This study identifies salivary micro-transcriptome features with differential expression among children with ASD-related GI disturbance. A subset of the RNAs displays relationships with treatment modality and are associated with autistic behaviors. The pathobiologic targets of the micro-transcriptome markers may serve as targets for individualized therapeutic interventions aimed at easing pain and behavioral difficulties seen in ASD-related GI disturbance.